AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN READING LONG ENGLISH TEXT - Yohana Triana Ina Weran; Agustinus Marjun; Yosefin Resti Damayanti (Suluh Adiluhung Publisher (SAPub), 2026)
Reading comprehension difficulties experienced by students can be attributed to two main factors: internal and external factors. Limited vocabulary knowledge is one of the difficulties students face when reading English texts. Many students have limited English vocabulary, which can make it difficult for them to understand the meaning of the texts they read. This research was conducted using a qualitative method, with a questionnaire as the data collection technique. The questionnaire was distributed to fourth-semester students of the English Education Study Program at the University of Kapuas. Based on the respondents’ answers, the findings indicate that the length of the text itself was not necessarily the main difficulty. Instead, students experienced greater difficulties in understanding the content of the text. Therefore, students’ difficulties in reading long English texts may be influenced not only by the length of the texts but also by their ability to comprehend the content and maintain their interest and concentration while reading.